Intellectual property law and development in Namibia: harnessing the law on geographical indications in the realization of vision 2030 - Ihuhua, Lineekela (Department of Commercial Law, 2024)
Intellectual property involves the creation of the mind with commercial and/or moral value. Geographical Indications (GI) are a species of intellectual property. A GI is a sign used to identify a product's origin. Furthermore, it indicates the product's quality, characteristics, and reputation associated with that territory or origin. GI rights themselves also have the potential to drive economic development. The thesis considers the absence of a sui generis system for the protection of GIs in Namibia, thereby entreating a discourse on whether there is a need for a stand-alone GI framework. The thesis also sets out the national and international framework for trademark protection as this is one of the vehicles some countries, including Namibia, have opted to use to protect GIs. Additionally, a comparative examination of the approaches of South Africa and India in the protection of GIs is undertaken to provide the various available, as well as potential, regimes for GI protection in Namibia. The thesis correspondingly sets out the role that GI protection can play in advancing Namibia's developmental objectives. It is postulated that GIs are a tool that can be used to advance the developmental objectives of Namibia as set out in the Vision 2030 and Harambee Prosperity Plans. The thesis establishes that GIs in Namibia find protection through the application of trademark laws; however, there is limited specific reference and consideration paid to GI promotion in the formulated developmental objectives of Namibia. The findings in the thesis, therefore, call for a need to incorporate GI protection and promotion in the country's developmental policy objectives. This alignment of law and objectives will enable the full realisation of the developmental potential of GIs in Namibia.